Microprocessor architecture, programming, and applications with the 8085 - Gaonkar, Ramesh S (Prentice Hal, 2002)
The first of its kind to offer an integrated treatment of both the hardware and software aspects of the microprocessor, this comprehensive and thoroughly updated book focuses on the 8085 microprocessor family to teach the basic concepts underlying programmable devices. A three-part organization covers concepts and applications of microprocessor-based systems: hardware and interfacing, programming the 8085, and interfacing peripherals (I/Os) and applications.